2013
DOI: 10.1007/s11255-013-0615-8
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular hypertrophy and chronic fluid overload in peritoneal dialysis patients

Abstract: Overhydration is strongly associated with LVH in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Although cautious interpretation is warranted given the small number of cohorts including echocardiogram data, our findings add weight to the developing narrative that cardiac structural disease, particularly left ventricular systolic dysfunction (LVSD), may not be the sine qua non underlying excess mortality in overhydrated ESKF patients. The link between BI-OH and adverse cardiovascular events has been previously noted; BI-OH previously being correlated with endothelial dysfunction 72 , arterial stiffness 43 and the development of left ventricular hypertrophy (LVH 73 , 74 ). In studies exploring sudden cardiac death in ESKF, LVH was predictive of mortality even when adjusting for blood pressure, whereas LVSD played no such role in predicting mortality.…”
Section: Discussionmentioning
confidence: 96%
“…Although cautious interpretation is warranted given the small number of cohorts including echocardiogram data, our findings add weight to the developing narrative that cardiac structural disease, particularly left ventricular systolic dysfunction (LVSD), may not be the sine qua non underlying excess mortality in overhydrated ESKF patients. The link between BI-OH and adverse cardiovascular events has been previously noted; BI-OH previously being correlated with endothelial dysfunction 72 , arterial stiffness 43 and the development of left ventricular hypertrophy (LVH 73 , 74 ). In studies exploring sudden cardiac death in ESKF, LVH was predictive of mortality even when adjusting for blood pressure, whereas LVSD played no such role in predicting mortality.…”
Section: Discussionmentioning
confidence: 96%
“…Hypohydration in older adults living in the community is widely considered to be common (24), although some contention exists within the literature as to the accuracy of these beliefs (10). Hyperhydration is considered rare in otherwise healthy individuals, with the majority of reports of excess body fluid due to polydipsia (intake >3 liters fluid per day) associated with mental illness (25, 26) or those undergoing medical care as in diabetes and dialysis (2729). …”
Section: Water In the Bodymentioning
confidence: 99%
“…These results lead to the opinion that besides inadequate removal of uremic toxins, overhydration could still be the main mechanism for progression of LVH in our study patients. Recently, Cader et al clearly demonstrated that the overhydration is strongly associated with LVH in PD patients [19]. Furthermore, a recent study during a 6-month follow-up further supports the presumption of positive effect of volume control in dialysis patients using clinical routine by segmental calf bioimpedance spectroscopy (cBIS) for dry weight assessment.…”
Section: Discussionmentioning
confidence: 86%